School Quality Enhancement in Secondary Education: Multi-Level School-Based Strategies and Insights That Contribute to Educational Improvement - Belina, Debeli; Geleta, Abeya; Beyene, Desalegn; Tafesse, Mebratu (Journal of Education and Learning Environments, 2026)
Enhancing school quality requires a comprehensive and multifaceted approach that strengthens interconnected dimensions of the education system, ranging from resource allocation to instructional practices. This review synthesizes multi-level strategies in secondary education that contribute to improvement, emphasizing educational inputs, school-level processes, and classroom-centered practices. Drawing on evidence-based research and global best practices, the analysis highlights that in resource-constrained contexts, foundational investments such as adequate infrastructure, instructional materials, and qualified personnel are indispensable starting points. These investments establish the conditions necessary for effective teaching and learning. Community engagement further amplifies limited resources, promotes local ownership, strengthens accountability, and provides support structures that reinforce school effectiveness, ensuring that schools remain responsive to local needs. At the school level, strategic planning through improvement plans, continuous professional development, fostering a positive school climate, and effective leadership emerge as critical processes for sustained progress. Leadership that is collaborative and adaptive plays a central role in aligning resources with priorities and motivating staff. At the classroom level, key strategies include optimizing instructional time, expanding learning opportunities, and monitoring student progress to ensure equitable outcomes. These practices directly influence student achievement and help bridge gaps in learning. The review underscores that a holistic, context-sensitive approach integrating foundational inputs with process improvements at both the school and classroom levels is vital for sustainable and inclusive educational transformation. These insights provide practical guidance for policymakers, school leaders, and educators committed to fostering meaningful and lasting improvements in school quality and effectiveness.